(untitled) (Bangladesh Journal of Botany, 2025)
This study aims to examine the influence of three categories of environmental factors-climatic, soil and topographic conditions, on millet quality in the eastern and western regions of the Lyuliang Mountains. Ten millet varieties were assessed across 15 quality indices, including protein, fat, and essential amino acids, at five locations on the eastern and western slopes of the Lyuliang Mountains. Comprehensive environmental data related to each sample site were collected. Principal component analysis (PCA) and correlation analysis were employed to explore the relationships between ecological factors and the nutritional composition of the millet. The results showed that certain nutrients in the millet were significantly correlated with specific environmental factors. Millet from Xingxian County exhibited the highest quality, with nutrient composition variation remaining below 10%. Environmental factors played a more substantial role in determining millet quality than genetic varieties. Average daily temperature showed a significant negative correlation (P <0.01) with protein and yellow pigment content, while demonstrating a positive correlation with branched-chain starch and phosphorus levels in millet. It was significantly (P <0.01) correlated with the content of flavonoids in millet by precipitation, significantly correlated with the content of methionine, isoleucine, leucine, and essential amino acids at the average daily temperature, and significantly (P <0.01) correlated with the content of threonine, isoleucine, leucine, and essential amino acids at the average daily temperature. Altitude had a significant negative correlation (P <0.01) with threonine content. The results of this study offer valuable guidance for selecting the finest varieties of millet and planting methods. Bangladesh J. Bot. 54(3): 509-517, 2025 (September)